Acidemia Can Occur Despite Category I Tracing - Bruno, Ann M.; López, Julia D.; Stout, Molly J.; Tuuli, Methodius G.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2020)
Objective Electronic fetal monitoring (EFM) is intended to assess fetal well-being during labor. Our objective was to test the hypothesis that findings of a category I tracing at any time in the 60 minutes prior to delivery would rule out neonatal acidemia.Study Design This was a planned secondary analysis of a single-center prospective cohort study of 8,580 singleton pregnancies undergoing labor with nonanomalous infants at term. Monitoring was reviewed by obstetric research nurses at 10-minute intervals in the 60 minutes prior to delivery. The primary outcome was acidemia, defined as an umbilical cord arterial pH of 7.10 or less.Results Of the 4,274 patients included, 42 (0.98%) infants had acidemia at birth. Of the 42 infants with acidemia, 13 (31%) had category I tracings in the 30 minutes prior to delivery. Three (7%) infants had neonatal acidemia despite category I tracing for >40 minutes in the 60 minutes prior to delivery.Conclusion Even in the presence of category I tracing in the 60 minutes prior to delivery, neonatal acidemia can still occur. Periods of category I should be interpreted within the clinical context of a priori risk for acidemia, knowing that it does not completely rule out acidemia.
Keywords: category I tracing; electronic fetal monitoring; neonatal academia; neonatal outcomes